A network of small protected areas favoured generalist but not specialized wetland birds in a 30-year period. (August 2020) - Brambilla, Mattia; Rizzolli, Franco; Franzoi, Alessandro; Caldonazzi, Michele; Zanghellini, Sandro; Pedrini, Paolo
Abstract: Protected areas (PAs) have been established to promote the long-term conservation of biodiversity and ecosystems. Wetlands, which represent a key habitat worldwide, have been largely destroyed, particularly in more industrialized countries, and their remnants are now often preserved by PA networks, especially in the European Union. We tested the effectiveness of a PA network of 26 small wetlands in preserving wetland birds over a thirty-year period (1989–2019), by investigating changes in species occurrence and relating them to the species' ecological specialization. Out of 23 species, 10 showed an increase in occurrence, 7 remained stable and 6 declined. The number of occupied habitats (between 1 and 8) was significantly associated with the species' trend: specialized species decline, whereas generalists increased. Species with increasing occurrence mostly included common birds, whereas the declining ones were all species with an unfavourable conservation status at the national level. Generalist species increased their occurrence rates, whereas species with stricter, more specialized requirements, generally underwent contraction, suggesting that the conservation of isolated wetlands, managed according to criteria not strictly focused on birds, is not enough to preserve the more specialized species. The proper management of key habitats and the increase of ecological connectivity in the wetland system are crucial for the conservation of wetland-specialist birds. Graphical abstract: Unlabelled Image Highlights: We assessed the effectiveness of a network of 26 small wetland PAs in N Italy. We considered the occurrence of wetland birds over the period 1989–2019. Out of 23 species, 10 increased, 7 remained stable and 6 declined. Wetland-specialist birds declined, whereas wetland-generalists increased. Key habitats and connectivity of wetland system are crucial for habitat specialists.